The Effects of COVID-19 Pandemic on Social Media Usage in the Context of Uses and Gratification Approach - Hatice Tuzcu; Yasemin Bilişli (Türkiye İletişim Araştırmaları Dergisi)
The COVID-19 pandemic affected the whole world, threatened individuals physically, mentally andsocially, and considerably transformed their lifestyles in varying ways. Considering the spread of thedisease and affected age groups, the struggle with COVID-19 should not be limited to the medicalaspect but should also be addressed socially. The present study attempted to reveal how the usageof social media has been modified during the pandemic by drawing attention to the aspects of theCOVID-19 pandemic that affected social life. The general aim of the study is to examine the purposesand motivations of the individuals’ social media usage during the pandemic with reference to Uses andGratification approach. The research was carried out with 12 university graduate female participantsover the age of 50, who were determined by snowball sampling method. The findings obtained in thisstudy showed that the participants increased their usage of social media during the pandemic comparedto their previous engamenents with social media. Moreover, some of the participants increased theirusage of social media to reach news about COVID-19 faster, which pointed out their motivation to usesocial media for obtaining accurate information. Finally, the most important change in the participants’usage of social media was about their Twitter engagements. The results show that covid-19 has changedsocial media usage and also points to the power of social media.